2015
DOI: 10.1002/ejic.201500177
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of a 1,2‐Diphospholide by Double C–H Deprotonation

Abstract: Rapid testing of hydrophilic and hydrophobic basic immobilized amine sorbents (BIAS) for CO2 capture stability under practical conditions was achieved by direct contact of the sorbents with flowing liquid water. Losses in both CO2 capture capacity and amine content of sorbents after exposure to 0.5 mL min−1 of H2O at 25 °C for 40 min followed similar trends as losses observed after exposure to N2/steam (105 °C, 7 % H2O) for 10 h. We also found that hydrophobic TMPED helped stabilize sorbents to H2O, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The identity of 6 is further supported by 1 H NMR and 1 H– 31 P HMBC spectroscopic studies, which show that the proton resonance at δ = 10.30 (d, 3 J PH = 3.5 Hz) can be assigned to the C–H of the 5-membered ring of 6 . In our previously published work we showed that the reaction of n BuLi/As­(NMe 2 ) 3 with MesPH 2 gives the arsenic–phosphorus heterocycle 4,6-dimethylbenzo-1-arsa-2-phospholide, an arsenic analogue of antimony heterocycle 6 . The NMR spectroscopic characteristics of the [Li­(TMEDA) 2 ] + salt of the arsenic anion are similar to 6 , displaying a singlet resonance at δ = 175.7 ppm in the 31 P NMR spectrum and a singlet at δ = 9.01 in the 1 H NMR spectrum, for the C–H of the 5-membered ring.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The identity of 6 is further supported by 1 H NMR and 1 H– 31 P HMBC spectroscopic studies, which show that the proton resonance at δ = 10.30 (d, 3 J PH = 3.5 Hz) can be assigned to the C–H of the 5-membered ring of 6 . In our previously published work we showed that the reaction of n BuLi/As­(NMe 2 ) 3 with MesPH 2 gives the arsenic–phosphorus heterocycle 4,6-dimethylbenzo-1-arsa-2-phospholide, an arsenic analogue of antimony heterocycle 6 . The NMR spectroscopic characteristics of the [Li­(TMEDA) 2 ] + salt of the arsenic anion are similar to 6 , displaying a singlet resonance at δ = 175.7 ppm in the 31 P NMR spectrum and a singlet at δ = 9.01 in the 1 H NMR spectrum, for the C–H of the 5-membered ring.…”
Section: Resultssupporting
confidence: 90%
“…The synthesis of compounds 2 – 4 was achieved according to Scheme (see the Experimental Section). Our previous studies of 1 , showed that this reaction involving C–H activation of the o -CH 2 groups occurs via a series of oligo-phosphorus intermediates …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations